Biological traits of Glossogobius giuris (Hamilton, 1822) in a wetland ecosystem (Northwestern Bangladesh): Implications for sustainable fisheries management (Research in Agriculture Livestock and Fisheries, 2026)
The freshwater goby, Glossogobius giuris, is abundant in freshwater ecosystems across Bangladesh. The current investigation focuses on the population structure, growth pattern, and biological traits of G. giuris (Hamilton, 1822) in the Beel Kumari wetland habitat in Northwestern Bangladesh. A total of 542 specimens were collected during various trips in 2023 (excluding June to August, the breeding season) using gill nets. Biometric analyses were carried out to evaluate the length frequency distributions, LWR, and LLRs. Also, allometric condition factors (KA), Fulton’s condition factor (KF), and relative condition index  (KR) were examined. The growth of G. giuris was established as negatively allometric (b= 2.87), and their condition factors indicated a reasonably well-fed, healthy population (KA = 0.0119 ± 0.001, KF = 0.9597 ± 0.110; KR =1.0162 ± 0:113). The form factor (a3.0 = 0.0078) indicated that this species had adapted to the wetland environment. Total length and standard length had a significant linear relation (p